Fiscal Analysis and Governance of the City Council of Penang Island 2002-2011 - Katahenggam, Nagathisen (School of Social Sciences, USM, 2017)
Local governments make up the tier of governance that is closest to the masses. The inability of local governments to be financially secure was one of the reasons that saw the reorganization of local councils in Malaysia in 1976. Currently, there are still several councils that struggle with budgetary constraints, hence allowing for the federalization of certain functions of the local government. This paper looks into the financial position of Majlis Bandaraya Pulau Pinang for the duration of 2002-2011 based on an analysis of the council's Annual Reports. A general trend analysis on revenue and expenditure is employed in this study. Additionally, the rationale for certain expenditure and causes for reduced revenue are also elaborated. Assessment of the financial reports shows a surplus budget is achieved by the council for the duration of the study. Methods such as Public-Private Partnership and collaborative governance is also seen to be stabilizing factors that aid in improved budgetary management. Also noted, the expansion of the role of MBPP regarding the governance of George Town World Heritage Site and the requirement for a paradigm shift in the governing model of the council is also addressed. Moreover, a political shift in the management of the council is also noted to be a factor in its financial health.